Respon Imunogenitas Protein Permukaan 19 kDa Streptococcus pneumoniae (Immunogenicity Response of Streptococcus pneumoniae 19 kDa Surface Protein) - Muhammad Dimas Arya Candra Permana; Dini Agustina; Bagus Hermansyah (Pustaka Kesehatan, 2015)
Pneumonia is the main common cause of children death in the world. Microbiological studies found the major causes of pneumonia is Streptococcus pneumoniae. Infection of S.pneumoniae influenced by several virulence factors, one of which is surface protein. The purpose of this study was to determine the immunogenicity of 19 kDa S.pneumoniae surface protein through hemagglutination inhibition and adhesion inhibition test. Adhesion inhibition test used antibodies that is formed from surface protein, to inhibit bacterial adhesion to the enterocytes. Hemagglutination inhibition test also used antibodies that formed from surface protein, to inhibit the agglutination of erythrocytes caused by S.pneumoniae. The results showed that antibodies, which was formed from 19 kDa S.pneumoniae surface protein, were able to inhibit hemagglutination process up to 1X dilution. Adhesion inhibition test showed that the higher antibody dilution, the greater the adhesion index. Pearson correlation analysis of the adhesion test showed that there was a significant correlation between antibody dilution with bacterial adhesion index (R= -0,787; p=0,036). It can be concluded that the 19 kDa surface protein of S.pneumoniae was immunogenic.   Keywords: Streptococcus pneumoniae, surface protein, antibody